Tlingit seal hunters hut on beach, Yakutat Bay, Alaska, 1899 - Curtis, Edward S., 1868-1952
Small hut on beach, with stretched hides in frames laying on roofs and along sides of hut. Other huts with canoes pulled up on shore can be seen in background Caption on image: Curtis x255a. Copyrighted 1899. E. H. Harriman Caption on mount: Sealer's camp, Yakutat Bay. PH Coll 484.AB3